FUNCTIONAL CONNECTING OF TEACHINGS OF SERBIAN LANGUAGE AND LITERATURE - Љиљана Е. Петровачки (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
In this paper, we underline the need for functional connecting of the teachings of Serbian language and literature with the goal of more succesful understanding and interpretation of the literature and students' improved culture of expression. For explicational purposes, we solved several lexicological and cultorological problems observed in the structure and the semantics from the pieces of the folcloric literature. Their solutions show how broader linguo-culturological approaches to philological disciplines in general have successful application in didactical purposes as well.